Sosialisasi Perlindungan Hukum Terhadap Guru dari Kriminalisasi di SMAN 9 Bekasi - Nining Yurista Prawitasari; Akbar Sayudi; Abdul Latif (LPPI UMN AL WASHLIYAH, 2025)
This activity aims to improve public understanding, with the main focus on teachers and teaching staff at SMAN 9 Bekasi. Legal protection for teachers from criminalization has been achieved through various regulations that provide a legal basis in carrying out their duties and responsibilities as teachers. In Indonesia, the criminalization of teachers arises due to differences in views between parents and schools, especially regarding the role of teachers as educators. Disciplinary actions such as pinching, flicking, running in the school area, cleaning the school environment, and other forms of discipline are considered by parents to be human rights violations under the Child Protection Act. On the other hand, teachers perceive such actions as part of the pedagogical method. Criminalization of teachers leads to a decrease in confidence in their professionalism, so that teachers only carry out their duties as teachers and neglect their role as educators. The importance of the teacher's role is not only to teach in the classroom, but also to educate students about ethics and moral values is very significant. This is a key element in the effort to produce a generation that is not only intellectually smart but also has good character. It is expected that the results of this extension activity can provide a sense of security to teachers, so that they can focus on educating the next generation without worrying about unwarranted criminalization.